Est-il possible de determiner des criteres et indicateurs de gestion durable des forets tropicales? - Karsenty, A.; Lescuyer, G.; Nasi, Robert (2005)
Due to the need for forest certification, the criteria and indicators for sustainable management of tropical forests have tended to operate more and more as standards, with criteria holding pride of place as compared to indicators. In practice, they are used as the definition of sustainability applied on the scale of the individual management unit. The definition of sustainability criteria and concensus thereupon raises a number of unsolved issues concerning acceptable thresholds, scales of assessment and trade-offs required to draw together the three dimensions of sustainability (ecological, social and economic), which depend on how the various stakeholders construe sustainability. A clearer distinction needs to be made between criteria, whose effectiveness derives from the social endorsement afforded by certification, and indicators which are more useful in measuring how natural and social systems evolve with reference to a more dynamic conception of sustainability.